Use of Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes to Predict the Cardiotoxicity Potential of Next Generation Nicotine Products - Simms, Liam; Yu, Fan; Palmer, Jessica; Rudd, Kathryn; Sticken, Edgar Trelles; Wieczorek, Roman; Chapman, Fiona; Czekala, Lukasz; Stevenson, Matthew; O’Connell, Grant (Frontiers in Toxicology, 2022)
Combustible cigarette smoking is an established risk factor for cardiovascular disease. By contrast, the cardiotoxicity potential of non-combustible next generation nicotine products (NGPs), which includes heated tobacco products (HTPs) and electronic vaping products (EVPs), and how this compares relative to combustible cigarettes is currently an area of scientific exploration. As such, there is a need for a rapid screening assay to assess this endpoint. The Cardio quickPredict is a metabolomics biomarker‐based assay that uses human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) to screen for potential structural and functional cardiac toxicants based on the changes of four metabolites, lactic acid, arachidonic acid, thymidine, and 2’-deoxycytidine. The study aims were to investigate the cardiotoxicity potential of NGPs compared to cigarettes, in addition to nicotine. To accomplish this, hiPSC-CM were exposed to smoke or aerosol bubbled PBS samples: reference cigarette (1R6F); three variants of HTP; and three EVP variants. The 1R6F bPBS was the most active, having cardiotoxic potential at 0.3-0.6% bPBS (0.4 - 0.9 µg/mL nicotine), followed by HTP, which displayed cardiotoxic potential at a 10 times higher concentration, 3.3% bPBS (4.1 µg/mL nicotine). Both 1R6F and HTP bPBS (at 10-fold higher concentration than 1R6F) affected all four predictive metabolites, whereas none of the EVP bPBS samples were active in the assay up to the maximal concentration tested (10% bPBS). Nicotine tested on its own was predicted to have cardiotoxic potential at concentrations greater than 80 µg/mL, which is higher than expected physiological levels associated with combustible cigarette smoking. The application of this rapid screening assay to NGP research and the associated findings adds to the weight-of-evidence indicating that NGPs have a tobacco harm reduction potential when compared to combustible cigarettes. Additionally, this technique was shown to be sensitive and robust for the assessment of different NGPs and may be considered as part of a larger overall scientific framework for NGP assessments.